Effects of nanoencapsulation and PEGylation on biodistribution of indocyanine green in healthy mice: quantitative fluorescence imaging and analysis of organs - Bahmani B (Dove Medical Press, 2013)
Baharak Bahmani,1 Christian Y Lytle,2 Ameae M Walker,2 Sharad Gupta,1 Valentine I Vullev,1 Bahman Anvari1 1Department of Bioengineering, 2Division of Biomedical Sciences, University of California, Riverside, CA, USA Abstract: Near-infrared nanoconstructs present a potentially effective platform for site-specific and deep tissue optical imaging and phototherapy. We have engineered a polymeric nanocapsule composed of polyallylamine hydrochloride (PAH) chains cross-linked with sodium phosphate and doped with indocyanine green (ICG) toward such endeavors. The ICG-doped nanocapsules were coated covalently with polyethylene glycol (5000 daltons) through reductive amination. We administrated the constructs by tail vein injection to healthy mice. To characterize the biodistribution of the constructs, we performed in vivo quantitative fluorescence imaging and subsequently analyzed the various extracted organs. Our results suggest that encapsulation of ICG in these PEGylated constructs is an effective approach to prolong the circulation time of ICG and delay its hepatic accumulation. Increased bioavailability of ICG, due to encapsulation, offers the potential of extending the clinical applications of ICG, which are currently limited due to rapid elimination of ICG from the vasculature. Our results also indicate that PAH and ICG-doped nanocapsules (ICG-NCs) are not cytotoxic at the levels used in this study. Keywords: cancer, fluorescent imaging, nanoprobes, near infrared, pharmacokinetics, phototherapy, vascular imaging